Praktik Perawat Tentang Manajemen Nyeri Postoperasi Di Kabupaten Kebumen, Jawa Tengah Indonesia - Nugroho, Fajar Agung (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2018)
Objective: this article was to describe nurses’ practice regarding postoperative pain management in Kebumen, IndonesiaMethod: a descriptive survey design was used in this study. The sample consisted of 65 bachelor nurses who were working in the postoperative wards of five hospitals and selected by convenience sampling. However, only 63 nurses returned the questionnaires. The instrument in this study developed by the researcher and had passed reliability process by involved the five experts. The data collected from October to November 2015. Spearman’s correlation used to determine the correlations between demographic data with nurses’ practice.Result: this study found that most of the subjects (66.7%) had a moderate level of practice (regarding postoperative pain management). There was no significantly between demographic data and practice. The others findings indicated that there was a significantly positive correlation between age and duration of working experience. On the other hand, there was a significantly negative correlation between duration of working experience and types of pain experienced by the nurse.Conclusion: the nurses showed that had a moderate level of postoperative pain management.